2012
DOI: 10.1055/s-0032-1326955
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Nervous System Impairment in Gastroschisis

Abstract: Introduction After surgical repair of gastroschisis, most neonates exhibit severe intestinal dysmotility. We hypothesized that impaired development of the enteric nervous system or interstitial cells of Cajal (ICC) network contributes to impaired intestinal motility in gastroschisis. We evaluated this hypothesis in a rat model of gastroschisis. Material and Methods Gastroschisis was created surgically in rat fetuses on gestational day 18, under general anesthesia, and small bowel was harvested on day 22. Intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…As the pregnancy with gastroschisis progresses, the bowel usually becomes coated in an inflammatory fibrinous peel, resulting in thickening of the bowel wall, decreased bowel motility and possible luminal obstruction [4][5][6]. Several studies have demonstrated neuronal immaturity in animal models of gastroschisis that might explain the postnatal dysmotility observed in some of the patients with gastroschisis [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…As the pregnancy with gastroschisis progresses, the bowel usually becomes coated in an inflammatory fibrinous peel, resulting in thickening of the bowel wall, decreased bowel motility and possible luminal obstruction [4][5][6]. Several studies have demonstrated neuronal immaturity in animal models of gastroschisis that might explain the postnatal dysmotility observed in some of the patients with gastroschisis [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Disorders such as gastroschisis 41 may result in diarrhea by various mechanisms, including impaired motility, 42 surgical formation of ostomies that shorten bowel length, or bacterial overgrowth. Patients with gastroschisis can also acquire SBS as a result of volvulus that can occur before or after birth.…”
Section: Classification and Pathophysiology Of Diarrhea In Infants: Amentioning
confidence: 99%
“…It has been suggested that gastroschisis may be unfavored in terms of adaptation by the underlying severe dysmotility [ 63 ]. In animal models, gastroschisis is associated with hypertrophy and hyperplasia of both the circular and longitudinal muscle layers [ 64 , 65 ] and to a late differentiation of the intestinal cells of Cajal [ 66 ], which can all explain the dysmotility. Gastroschisis accounted for one third of the indications of AGIR and STEP and that suggests that such patients may be more prone to develop dilation as a consequence of dysmotility, than other primary diagnoses of SBS.…”
Section: Discussionmentioning
confidence: 99%